2017
DOI: 10.7717/peerj.4062
|View full text |Cite
|
Sign up to set email alerts
|

A 16-gene signature predicting prognosis of patients with oral tongue squamous cell carcinoma

Abstract: BackgroundOral tongue squamous cell carcinoma (OTSCC) is the most common subtype of oral cancer. A predictive gene signature is necessary for prognosis of OTSCC.MethodsFive microarray data sets of OTSCC from the Gene Expression Omnibus (GEO) and one data set from The Cancer Genome Atlas (TCGA) were obtained. Differentially expressed genes (DEGs) of GEO data sets were identified by integrated analysis. The DEGs associated with prognosis were screened in the TCGA data set by univariate survival analysis to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…To further compare the performance among diverse predictive models established from the publicly available TCGA data set, we reviewed the relevant literature and identified three models based on mRNA or lncRNA abundance in OSCC samples (Qiu et al, ; C. Zhao, Sun, Zeng, & Cui, ; X. Zhao et al, ). As listed in Table S5, our AS predictive models seemed superior to these three models as evidenced by the AUC values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further compare the performance among diverse predictive models established from the publicly available TCGA data set, we reviewed the relevant literature and identified three models based on mRNA or lncRNA abundance in OSCC samples (Qiu et al, ; C. Zhao, Sun, Zeng, & Cui, ; X. Zhao et al, ). As listed in Table S5, our AS predictive models seemed superior to these three models as evidenced by the AUC values.…”
Section: Resultsmentioning
confidence: 99%
“…-h). The model with the integrative 7 types of AS events had a superior predictive ability as compared to models with individual AS event, as evidenced by the AUC value of 0.7(Figure 6i).To further compare the performance among diverse predictive models established from the publicly available TCGA data set, we reviewed the relevant literature and identified three models based on mRNA or lncRNA abundance in OSCC samples(Qiu et al, 2017; …”
mentioning
confidence: 99%
“…The gene EVI2A, as the human homolog of mouse genes, may be associated with other proteins in the membrane as a part of a cell surface receptor complex [ 37 ]; EVI2A has been shown to be an oncogene [ 38 ]; EVI2A is highly expressed in oral tongue squamous cell carcinoma [ 39 ] and osteosarcoma [ 40 ] and is a risk factor for cancer prognosis. In this study, we found that EVI2A is one of the MDG of ccRCC, and its hypomethylation leads to poor prognosis ( Figure 9(d) ).…”
Section: Discussionmentioning
confidence: 99%
“…OSCC is an aggressive malignancy of the head and neck, with a 5-year survival rate of 40-50% worldwide (20,21). Although great efforts have been made over the past few decades to develop signatures for prognostic predictions, the lack of specificity and sensitivity to predict survival remains due to the complex molecular and cellular heterogeneity of OSCC.…”
Section: Discussionmentioning
confidence: 99%